Discourse and professional identities in healthcare communication - Emerson, Tristan (2021)
This study examines how professional identities are enacted in discourse; how clinicians convey their professional expertise and navigate the asymmetries that occur between expert and lay speakers in healthcare dyads. Utilising an innovative mixed-methods approach that combines corpus linguistics and discursive pragmatics with ethnography, two distinct healthcare corpora are analysed: The simulated consultations of a pedagogic training programme for general practice trainees, and the real-life consultations of primary care- based clinical pharmacists – a novel professional role that has not yet seen examination of its communicative practices. Analysis of the two datasets identifies that the GP trainees enact a performative certainty characterised by a disposition to state what ‘is’ within consultations, through realis moods, epistemic stances and commentary over contemporaneous states of affairs. Asymmetry is navigated by the trainees via recurrent strategies such as implicatures and wh-interrogative constructions previously identified as ‘invitations to input’ (Emerson et al. 2020). Examination of the clinical pharmacy data illustrates the clinical pharmacists’ utilisation of transactional irrealis constructions (characterised as ‘emphatic front staging’) to provide discursive evidence of work being concurrently undertaken, and to be undertaken in the future, for patient-centric purposes. The analysis argues that these formulations also operationalise a significant identity component, by dialogizing the remit of the new CP role and its alignment to the wider healthcare institution. Analysis of both datasets also considers how the meso-level, contextual detail apparent in each corpus effects the individual clinician’s identity performance. In line with the commitment to the collaborative, applied linguistics methodology taken, the thesis makes a number of recommendations for applied professional practice based upon the findings.